2018
DOI: 10.1111/tpj.14148
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis RRM domain protein EDM3 mediates race‐specific disease resistance by controlling H3K9me2‐dependent alternative polyadenylation of RPP7 immune receptor transcripts

Abstract: The NLR-receptor RPP7 mediates race-specific immunity in Arabidopsis. Previous screens for enhanced downy mildew (edm) mutants identified the co-chaperone SGT1b (EDM1) and the PHD-finger protein EDM2 as critical regulators of RPP7. Here, we describe a third edm mutant compromised in RPP7 immunity, edm3. EDM3 encodes a nuclear-localized protein featuring an RNA-recognition motif. Like EDM2, EDM3 promotes histone H3 lysine 9 dimethylation (H3K9me2) at RPP7. Global profiling of H3K9me2 showed EDM3 to affect this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Only at a small number of loci, such as RPP7 and IBM1 , such mechanistic details have been uncovered. In each of these cases, EDM2 serves as a chromatin binding protein, recruiting the RNA binding proteins ASI1/IBM2 and EDM3/AIPP1 to intronic heterochromatic regions [ 16 , 18 20 , 67 , 68 ]. Together with additional factors, such as AIPP2, AIPP3 and AIPP4 [ 19 ] the EDM2-containing complex controls alternative polyadenylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only at a small number of loci, such as RPP7 and IBM1 , such mechanistic details have been uncovered. In each of these cases, EDM2 serves as a chromatin binding protein, recruiting the RNA binding proteins ASI1/IBM2 and EDM3/AIPP1 to intronic heterochromatic regions [ 16 , 18 20 , 67 , 68 ]. Together with additional factors, such as AIPP2, AIPP3 and AIPP4 [ 19 ] the EDM2-containing complex controls alternative polyadenylation.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported the identification of EDM2-interacting proteins, which include EMSY-like nucleosome remodeling factors and the WNK8 protein kinase [ 15 , 17 ]. Besides this EDM2 has been shown to interact with the RNA binding proteins ASI1/IBM2 and EDM3/AIPP1 [ 19 , 20 ]. We further found that EDM2 controls silencing of some transposable elements (TEs) by modulating levels of di-methylated lysine 9 of histone H3 (H3K9me2), a ubiquitous TE silencing signal in plants [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the four amino acid changes between ‘Junam’ and ‘Samgwang’ exists in the second RRM domain. Interestingly, an Arabidopsis RRM domain protein, ENHANCED DOWNY MILDEW 3 (EDM3), reportedly mediates resistance to the downy mildew disease pathogen, Hyaloperonospora arabidopsis [25]. EDM3 controls the alternative polyadenylation of RPP7 resistance gene transcripts by suppressing proximal polyadenylation at a transposon insertion site in the first RPP7 intron.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the AAE complex is indispensable for the generation of full-length transcripts of genic heterochromatin-containing genes. Regarding the underlying mechanism, recent report indicates that EDM2 and AIPP1 mutations can slow down Pol II elongation rate at proximal polyadenylation site, leading to a promotion of proximal polyadenylation site usage ( Lai et al, 2019 ). AAE complex-mediated polyadenylation regulation plays an important role in multiple biological processes, including modulating plant immunity by targeting innate immunity receptor gene RPP7 ( Tsuchiya and Eulgem, 2013 ), epigenome regulation by targeting histone H3K9me2 demethylase gene IBM1 , and T-DNA suppression ( Saze et al, 2013 ; Wang et al, 2013 ).…”
Section: Chromatin-based Regulation Of Alternative Rna Processingmentioning
confidence: 99%